SOCIAL IMPACT OF CAROK ON OFFENDERS’ FAMILIES: A CRIMINOLOGICAL PERSPECTIVE IN SAMPANG - Mohammad Nuruddin (Acitya Wisesa: Journal of Multidisciplinary Research, 2025)
The settlement of carok as part of Madurese society is very important to analyze. This study aims to determine the social impact on the families of carok perpetrators in the perspective of criminology. The second objective is to determine the role of community leaders and the police in minimizing threats and taking preventive action against the families of carok perpetrators in Madura. The research method used in this research is the type of empirical legal research. The results showed that: First, from a criminological perspective, carok can be categorized as a crime. Carok in this case can be subject to articles of the Criminal Code related to crimes against the body and crimes against life. According to labeling theory, families of carok perpetrators are usually labeled by the community as families of criminals who are usually dubbed as “Kaloarga Tokang Carok”. Second, Kiai in carok cases plays a role in reconciliation and mediation efforts between the families of carok perpetrators and the families of carok victims to minimize threats to the families of carok perpetrators. The Sampang Police, among others, conducted counseling with the perpetrator's family and collaborated with community leaders.